2022
DOI: 10.1101/2022.12.13.22283400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long term anti-SARS-CoV-2 antibody kinetics and correlate of protection against Omicron BA.1/BA.2 infection

Abstract: Binding antibody levels against SARS-CoV-2 have shown to be correlates of protection against infection with pre-Omicron lineages. This has been challenged by the emergence of immune-evasive variants, notably the Omicron sublineages, in an evolving immune landscape with high levels of cumulative incidence and vaccination coverage. This in turn limits the use of commercially available high-throughput methods to quantify binding antibodies as a tool to monitor protection at the population-level. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[5][6][7] Feng et al demonstrated 80% protection against SARS-CoV-2 infection when the anti-S antibody level was 247 BAU/ml in a ChAdOx1 study cohort. During the Omicron BA.1/BA.2 epidemic period, reductions in infection risk were reported for anti-S antibody titers above 2000 BAU/mL, 800 BAU/mL, and 4810-11233 BAU/mL for symptomatic infections [9][10][11] Additionally, during the Omicron BA.4/5 epidemic period, reductions in infection risk were reported for anti-S antibody titers above 380-1560 BAU/mL, but the anti-S antibody titer thresholds varied according to previous infection histories, and the association between the anti-S antibody titers and the infection risk was not observed in individuals with previous Omicron BA.2 infection. 12 Our results did not estimate an 80% relative risk reduction against infection, even at anti-S antibody titers above 100,000 BAU/mL during the Omicron BA.5 epidemic period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Feng et al demonstrated 80% protection against SARS-CoV-2 infection when the anti-S antibody level was 247 BAU/ml in a ChAdOx1 study cohort. During the Omicron BA.1/BA.2 epidemic period, reductions in infection risk were reported for anti-S antibody titers above 2000 BAU/mL, 800 BAU/mL, and 4810-11233 BAU/mL for symptomatic infections [9][10][11] Additionally, during the Omicron BA.4/5 epidemic period, reductions in infection risk were reported for anti-S antibody titers above 380-1560 BAU/mL, but the anti-S antibody titer thresholds varied according to previous infection histories, and the association between the anti-S antibody titers and the infection risk was not observed in individuals with previous Omicron BA.2 infection. 12 Our results did not estimate an 80% relative risk reduction against infection, even at anti-S antibody titers above 100,000 BAU/mL during the Omicron BA.5 epidemic period.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] While the prevention of severe disease through vaccination has been confirmed even during the Omicron BA.1/2 and BA.4/5 epidemic periods 8 , higher anti-spike (S) antibody titers against the ancestral strain were required for protection against infection during these periods compared to the pre-Omicron epidemic period. [9][10][11][12] Omicron sublineages tend to be selected for mutations with high humoral immune evasion capabilities, 13 and the protective effect of anti-S antibody titers against the ancestral strain needs to be re-evaluated in response to changes in the antigenicity of the emerging variants. 14 Recently, with the increase in the proportion of infected individuals, it has been reported that not only the neutralizing antibody titers and anti-S antibody titers induced by vaccination but also past infection history are significantly associated with a reduction in infection risk.…”
Section: Introductionmentioning
confidence: 99%